2002
DOI: 10.1081/jfp-120005786
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Outliers Using Unsupervised Principal Component Similarity Analysis for Sensory Evaluation of Foods

Abstract: As unsupervised classifications, principal component similarity (PCS) and cluster analysis (CA) were compared for outlier detectability in panel evaluation. By rotating the reference, PCS can define outlying panelists based on the similarity of their evaluation patterns with that of the reference panelist. As a result, the outliers detected on PCS scattergrams are dependent on the reference selected, whereas, outliers detected by CA are based on dissimilarity, thus being rather unilateral. The definition of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Nakai et al 37 claimed that a human was able to classify objects, on the basis of a bi‐plot, better than a computer. By that, they confirmed the opinion of Buydens et al ,50 who stated that computer methods were still not able to recognise data patterns better than a human.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nakai et al 37 claimed that a human was able to classify objects, on the basis of a bi‐plot, better than a computer. By that, they confirmed the opinion of Buydens et al ,50 who stated that computer methods were still not able to recognise data patterns better than a human.…”
Section: Discussionmentioning
confidence: 99%
“…Although Vodovotz et al 35 reported lower classification accuracy of PCS compared with SDA, they concluded that the former is useful because it can be used with a small number of samples and has the capacity of detecting outliers. An application of PCS in detecting outliers is presented in the paper by Nakai et al 37…”
Section: Principal Component Similarity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For classification of uncharacterized sequences, the PCS scatterplots are also useful as shown in Figures 1, 5 and 7. The PCA demonstrated the classifying capacity superior to that of distance-based cluster analysis [39]. The PCS is more flexible than cluster analysis as different pattern similarity patterns can be drawn by rotating the reference segment for searching.…”
Section: Discussionmentioning
confidence: 99%
“…The method described in the previous papers [9,39] was followed. Principal components analysis (PCA) was modified to principal components similarity (PCS) by incorporating linear regression of PC scores to be able to account for more than three PC scores on a 2D scatter plot.…”
Section: Methodsmentioning
confidence: 99%